Canal Wall Down Tympanomastoidectomy and Facial Nerve Decompression in Patients with Facial Nerve Palsy Caused By Cholesteatoma-Type Chronic Suppurative Otitis Media - Leon Gaya; Jacky Munilson (Jurnal Otorinolaringologi Kepala dan Leher Indonesia, 2026)
Canal Wall Down Tympanomastoidectomy and Facial Nerve Decompression in Patients with Facial Nerve Palsy Caused By Cholesteatoma-Type Chronic Suppurative Otitis Media Background: Facial nerve palsy is a neurological complication that can occur in patients with chronic suppurative otitis media (CSOM) of the cholesteatoma type. Cholesteatoma can damage the facial nerve through mechanisms such as compression, erosion of the facial nerve canal, and chronic inflammation. Management of peripheral facial nerve palsy caused by cholesteatoma-type CSOM can be effectively achieved through surgical intervention. Case Report: A 36-year-old male presented with a 10-year history of discharge from the right ear, who developed right-sided facial paralysis classified as House-Brackmann grade V, with a lesion level at the geniculate ganglion due to cholesteatoma-type CSOM. The patient underwent Canal Wall Down (CWD) tympanomastoidectomy, including cholesteatoma excision, facial nerve decompression, underlay graft placement, and reconstruction of the ear canal wall. Conclusion: Facial nerve palsy is a complication of cholesteatoma-type chronic suppurative otitis media (CSOM), which can be caused by direct or indirect compression of the facial nerve. Surgical intervention with Canal Wall Down (CWD) tympanomastoidectomy, including complete cholesteatoma excision and indirect facial nerve decompression, provides a good recovery of nerve function.